SEM and PCR study of mycorrhizal fungi isolated from the Australian terrestrial orchid: Prasophyllum - McQualter, Emily (Universidad de Costa Rica, 2015)
Most members of the genus Prasophyllum (Leek Orchids) are threatened and restricted in distribution in Australia. Prasophyllum species are obligate mycotrophic plants and current conservation proto- cols for terrestrial orchids in Australia require propa- gation with symbiotic mycorrhizal fungi. Unfortunately there is a paucity of knowledge regard- ing the mycosymbiont in this genus, hampering con- servation and re-introduction efforts.